The role of perseverative cognition in the job strain-health outcome relationship - McCarrick, Dane; Prestwich, Andrew; O'Connor, Daryl B. (Psychology & health, 2024)
Objective: Job strain has been implicated in a variety of adverse health outcomes, particularly cardiometabolic and inflammatory diseases. However, the mechanisms underlying these effects remain largely unknown. One possibility is that the maladaptive coping response to stress, (perseverative cognition (PC); the cognitive representation of past stressful events (rumination) or feared future events (worry)), either in work or more generally, mediates the relationship between job strain and physical disease. The aim of this study was thus to test the potential role of both general, and work- related PC as a mediating, or potentially moderating, mechanism between job strain and ill- health outcomes. Design & Measures: Using an online cross- sectional design, 650 full- time employees completed measures of job strain, general and work- related PC (rumination & worry) and health outcomes (burnout, somatization, health behaviours & sleep quality). Results: General and work- related worry and rumination significantly mediated, often independently, the relationship between job strain and burnout, somatization, and sleep quality. No significant mediation effects were observed for health behaviours and no type of PC (general or work- related) moderated job strain- health outcome relations. Conclusion: Both general and work- related worry and rumination are likely to play important, and partly independent, roles in understanding the adverse relationships between job strain and various health outcomes.